Prevalence of small opacities in chest radiographs of nickel sinter plant workers. Issue 5 (May 1993) - Muir, D C; Julian, J; Jadon, N; Roberts, R; Roos, J; Chan, J; Maehle, W; Morgan, W K
Abstract : Radiographs from 745 nickel sinter plant workers were taken and classified by five readers using the International Labour Office (1980) protocol. Each reader worked independently and the films were randomly mixed with films from a non-dust exposed office population and also with films from subjects known to have silicosis or asbestosis. The prevalence of small irregular opacities was selected as the outcome of interest. In the sinter workers this was within the range identified in cigarette smokers or in workers exposed to dusts of low fibrogenicity. Only minimal evidence of small round opacities was noted. There was no evidence from the chest radiographs that exposures to high concentrations of dusts containing compounds of nickel caused an inflammatory or fibrogenic response in the lungs of the exposed population.